Socio-economic status and diabetes control in patients presenting to Princess Marina hospital (PMH), Gaborone, Botswana - Baruti, Violet (Stellenbosch : University of Stellenbosch, 2015)
Thesis (MMeD) -- Stellenbosch University, 2015 Thesis